The Evolution Of The Concept Of Freedom In Eastern And Western Philosophical Thought (Comparative Analysis) (Zien Journal of Social Sciences and Humanities, 2025)
The article presents a comparative analysis of the concept of freedom in Eastern and Western philosophical thought. It also explores the views of Eastern and Western philosophers on freedom. The role of freedom in Eastern and Western societies is examined